Strong Anisotropy of Multilayer γ‐InSe‐Enabled Polarization Division Multiplexing Photodetection. Issue 12 (17th August 2022) - Wang, Xusheng; Wen, Bo; Gao, Siyan; Li, Xiaolin; Lin, Zezhou; Du, Luping; Zhang, Xi
Abstract : Polarized light detection is consequential for optical communication and polarized light imaging. InSe is considered a promising candidate for narrow‐bandgap photodetector. However, monolayer γ‐InSe is an indirect bandgap semiconductor and is ignored for a long time for polarized light detection. In this work, by virtue of the indirect–direct conversation and the surface‐bound excitons, the intrinsic anisotropy of multilayer γ‐InSe is revealed by the photoluminescence (PL) measurement under polarized light. Due to the anisotropy of surface‐bound exaction and in‐plane exciton, there are significant differences in the photocurrent under irradiation of laser with different polarization angles. The γ‐InSe‐based photodetector exhibits considerable polarization‐dependent photocurrent with an outstanding anisotropic ratio of 2.7. Moreover, the multilayer γ‐InSe photodetector shows high responsivity of 7.47 A W −1 and specific detectivity of 4.56 × 10 13 Jones under 785 nm laser. Based on the InSe polarization photodetector, a polarization division multiplexing that can simultaneously process four information tracks and enhance the communication speed by 2 4 is explored. The multilayer InSe polarization photodetector proposed in this work broadens a new path for polarized light detection, and brings a potential solution to the field of optical communications. Abstract : An outstanding polarized light detector is prepared by multilayer γ‐InSe. With the intrinsic anisotropy of transition along the armchair and zigzag direction, the InSe photodetector exhibits an anisotropic ratio of photocurrent of 2.7, which enables polarized light imaging and polarization division multiplexing for optical communication.